2021
DOI: 10.1016/j.conctc.2021.100713
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of concealment, fabrication and falsification of study data by deceptive subjects

Abstract: Purpose Many studies have found evidence that research subjects engage in deceptive practices while participating in health-related studies. Little is known, however, about how often subjects use deception and the percentage of studies a typical subject will contaminate with false data. This study examined the frequency of use of different types of deception among a sample of subjects who admit to using deception. Methods A sample of 59 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…At best, the high value of significant findings gives luck an outsized role in determining a scientist’s success—a career that may require 10 or more years of post-baccalaureate training, during which time it is typical to earn limited wages. At worst, it encourages scientific fraud ( Fanelli, 2009 ; Devine et al, 2021 ). In any case, the Holy Grail of statistical significance serves as a linchpin for common missteps in preclinical research that will be discussed below—because, yes, we are rewarded for making such missteps and punished when we don’t.…”
Section: To Understand the Problem We Must Examine The Goal: How Publ...mentioning
confidence: 99%
“…At best, the high value of significant findings gives luck an outsized role in determining a scientist’s success—a career that may require 10 or more years of post-baccalaureate training, during which time it is typical to earn limited wages. At worst, it encourages scientific fraud ( Fanelli, 2009 ; Devine et al, 2021 ). In any case, the Holy Grail of statistical significance serves as a linchpin for common missteps in preclinical research that will be discussed below—because, yes, we are rewarded for making such missteps and punished when we don’t.…”
Section: To Understand the Problem We Must Examine The Goal: How Publ...mentioning
confidence: 99%
“…Research deception involves participants gainfully accessing research studies for financial incentives by self-reporting their inclusion criteria for the study when they are in fact impostors. Researchers have found that some participants changed their self-reported sexual orientation, biological sex, birthdate, as well as concealed or pretended to have a health condition to be eligible for surveys or clinical trial studies (Chandler & Paolacci, 2017;Devine et al, 2021;Glazer et al, 2021). Some of these potentially fraudulent participants have been identified through comparison of responses to previous surveys as well as identifying participants who exited a survey and reattempted to complete it with different information that met eligibility criteria (Chandler & Paolacci, 2017;Glazer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, one research team with Institutional Review Board approval used an Internet service to confirm participants' identity and found that 7% of applicants were deemed fraudulent and two people even supplied information from deceased individuals (Glazer et al, 2021). Another research team has been recruiting subjects who use deception and found that they openly admit to concealment, fabrication and falsification of information to enter studies (Devine et al, 2013(Devine et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation